Learning media of macromedia flash android-based and contains character education - Ahmad Yani; Adriana Nada Beta; Hodiyanto Hodiyanto; Rahman Haryadi (Jurnal Pendidikan Informatika dan Sains, 2023)
This study aimed to produce Macromedia flash learning media based on android and filled with effective, practical, and effective character education. This study adopts a 4D development design model, which includes four main stages, Define, Design, Develop, and Disseminate. The subjects of this research were students of class X SMA Graduation Pontianak. The data collection tools were validation sheets, questionnaires, and tests. The data analysis technique used is descriptive statistics. The results showed that the media validation results by the three experts were 78.5%, which is a very valid criterion. The cumulative score of the teacher and student questionnaire reached 93.71%, which is very practical. The results of the t-test show that t Stat > t Critical two-tail then H0 is rejected, which means H1 is accepted, so it can be concluded that the learning media Macromedia Flash 8 is classified as effective because there is an increase in student learning outcomes between before and after being given learning with Macromedia Flash 8 learning media based on android and loaded with character education.